The MtrCDE Efflux Pump Contributes to Survival of Neisseria gonorrhoeae From Human Neutrophils and Their Antimicrobial Components - Handing, Jonathan W.; Ragland, Stephanie A.; Bharathan, Urmila V.; Criss, Alison K. (Frontiers in Microbiology, 2018)
The mucosal inflammatory response to Neisseria gonorrhoeae (Gc) is characterized by recruitment of neutrophils to the site of infection. Gc survives exposure to neutrophils by limiting the ability of neutrophils to make antimicrobial products and by expressing factors that defend against these products. The multiple transferable resistance (Mtr) system is a tripartite efflux pump, comprised of the inner membrane MtrD, the periplasmic attachment protein MtrC, and the outer membrane channel MtrE. Gc MtrCDE exports a diverse array of substrates, including certain detergents, dyes, antibiotics, and host-derived antimicrobial peptides. Here we report that MtrCDE contributes to the survival of Gc after exposure to adherent, chemokine-treated primary human neutrophils, specifically in the extracellular milieu. MtrCDE enhanced survival of Gc in neutrophil extracellular traps and in the supernatant from neutrophils that had undergone degranulation (granule exocytosis), a process that releases antimicrobial proteins into the extracellular milieu. The extent of degranulation was unaltered in neutrophils exposed to parental or mtr mutant Gc. MtrCDE expression contributed to Gc defense against some neutrophil-derived antimicrobial peptides but not others. These findings demonstrate that the Mtr system contributes to Gc survival after neutrophil challenge, a key feature of the host immune response to acute gonorrhea.